Prevalence and factors associated with depression among boarding school students in Suratthani - T, Anantaseriwidhya; S, Punyapas; T, Hosiri (Biomedical Sciences and Clinical Medicine, 2021)
Objectives To determine the prevalence and associated factors of depression among boarding school students in Suratthani, Thailand. Methods A cross sectional study was carried out from 339 students randomly selected from boarding school in Suratthani using proportional stratified random sampling method. Depression and its asso-ciated factors were assessed by using Center for Epidemiological Studies-Depression Scale (CES-D) and Social support and life satisfaction scales respectively. Chi-square and multiple logistic regression were used to analyze the associated factors. Results The prevalence of depression among Suratthani boarding school students is 20.9% (CES-D ≥ 22). After adjusting by multiple logistic regression, depression significantly associated with female (AOR 2.528, 95%CI 1.133 to 5.637), lower Grade Point Average (AOR 0.215, 95%CI 0.074 to 0.624), being bullied > 5 times/week (AOR 2.528, 95%CI 1.133 to 5.637), poor teacher support (AOR 7.807, 95%CI 1.514 to 40.269), poor family support (AOR 29.448, 95%CI 3.003 to 288.788), moderate peer support (AOR 3.069, 95%CI 1.483 to 6.349). Conclusions The prevalence of depression among boarding school students in Suratthani was lower than previous study. However, the major associated factor of depression was poor family support. Thus, promotion family support, social support from peer and teacher, bullying prevention and academic performance might be beneficial for depression in boarding school students.